Indolent T‐lymphoblastic proliferation: A systematic review of the literature analyzing the epidemiologic, clinical, and pathologic features of 45 cases. (16th May 2022) - Saglam, Arzu; Singh, Kunwar; Gollapudi, Sumanth; Kumar, Jyoti; Brar, Nivaz; Butzmann, Alexandra; Warnke, Roger; Ohgami, Robert S.
Abstract: An indolent T‐lymphoblastic proliferation (iT‐LBP) is a rare benign disorder characterized by an abnormal expansion of immature T‐cells, which morphologically can mimic malignancy. Since the first case was described in 1999, dozens more have been reported in the literature. However, the epidemiologic, clinical, pathologic, and biologic features of this disease have not been well described. Here, we retrospectively reviewed all known cases reported in the literature to better understand this entity. A PubMed search up to January 2022 highlighted 25 papers describing cases/case series of iT‐LBP, one of which was a case presentation in a slide workshop. Except for 9 of the cases in one of the papers, where it was evident that the number of CD3+/TdT+ cells were too few to conform with a diagnosis of iT‐LBP, all papers and all the cases reported were included in the study amounting to a total of 45 cases. Clinicopathologic characteristics were analyzed using descriptive statistics and frequencies. Our analysis highlighted the previously known association with Castleman disease and Castleman‐like features and underlined its association with dendritic cell proliferations in general, as well as uncovering high frequency of concurrence with hepatocellular carcinoma and autoimmune diseases, most notably myasthenia gravis, paraneoplastic pemphigus and paraneoplastic autoimmune multiorgan syndrome. Furthermore, the co‐expression of CD4 and CD8 and high prevalence of extranodal disease and recurrences were other less well described features that were revealed.